Harmonisasi Tradisi Takhtīm Al-Qur’an dan Salat Tahajud - Lutfi, Moh; Ma’arif, Cholid; Ro’uf, Abdul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The Pesantren Hamalatul Qur'an Jombang offers a unique blend of religious tradition and worship rituals. This study, using qualitative and Living Qur'an research methods, delves into the community's daily practice of bringing the Qur'an to life. A key finding is the mandatory nightly tahajud prayer khataman activity, where students and worshippers recite 1/2 juz of the Qur'an collectively. This practice fosters a sense of community and loyalty to the pesantren's traditions. It also cultivates spiritual growth and seeks divine blessings for the students' Qur'an memorization journey. This harmonization of religious tradition and worship rituals demonstrates the pesantren's commitment to both individual spiritual development and collective community building. By integrating these practices, the pesantren creates a vibrant and inspiring environment for its students and the broader community.